Luxembourg : Staff Report for the 2004 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This 2004 Article IV Consultation highlights that the Luxembourg authorities are adjusting policies to the growth slowdown, although major new initiatives are on hold in the run-up to the June 2004 general election. Tax cuts, high expenditure, and weak activity are estimated to have caused a general government deficit in 2003. Executive Directors have welcomed indications that real GDP growth is rebounding, following an unusually long period of sluggish activity. However, they have stressed that medium-term growth prospects are now less buoyant in comparison with the exceptional growth performance of the past decade.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet